DOP42 Efficacy and safety of deucravacitinib, an oral, selective tyrosine kinase 2 inhibitor, in patients with moderately-to-severely active Ulcerative Colitis: 12-week results from the Phase 2 LATTICE-UC study. (21st January 2022) - Danese, S; Panaccione, R; D'Haens, G; Peyrin-Biroulet, L; Schreiber, S; Kobayashi, T; Gawdis-Wojnarska, B; Korga, P; Aguilar, H; Sharkey, B; Sreih, A; Radosti, C; et al.
Abstract: Background: Tyrosine kinase 2 (TYK2) is an intracellular kinase that mediates the signalling of key cytokines involved in ulcerative colitis (UC) pathophysiology. Deucravacitinib (DEUC) is a novel, oral, selective TYK2 inhibitor that binds to the TYK2 regulatory domain. The safety and efficacy of DEUC were evaluated in patients (pts) with moderately-to-severely active UC. Methods: LATTICE-UC (NCT03934216), a randomised, double-blind, placebo (PBO)-controlled, multicentre, Phase 2 trial, enrolled pts with moderately-to-severely active UC (modified Mayo score of 5 to 9 [endoscopic ES subscore ≥2, rectal bleeding RB subscore ≥1, stool frequency SF subscore ≥2) with inadequate response, loss of response, or intolerance to ≥1 conventional or biologic therapy. Pts were randomised 2:1 to oral DEUC 6 mg or PBO twice daily (BID) and stratified by baseline (BL) corticosteroid use and prior exposure to biologics. The primary endpoint was clinical remission (modified Mayo score with subscores of SF ≤1 with ≥1-point decrease from BL, RB=0, and ES ≤1 [modified, excludes friability]) at Week (Wk) 12; endoscopic response (ES ≤1) at Wk 12 was a secondary endpoint. Results: Demographic and BL characteristics were generally similar across groups, except for BL disease activity as measured by the modified Mayo score and ES subscore. Most pts (63.4%) were biologic naïve, and 40.5% were receiving concomitant oral corticosteroids (Table 1 ). Of 131 pts randomised, 104 (79.4%) completed 12 wks of treatment (DEUC, 69/87 [79.3%]; PBO, 35/42 [83.3%]). At Wk 12, clinical remission rates were 14.8% and 16.3% in the DEUC and PBO arms, respectively, in the overall population ( P =0.59); 14.0% and 25.9% in biologic-naïve pts; and 16.1% and 0.0% in biologic-experienced pts (Figure 1 ). At Wk 12, endoscopic response rates were 19.3% and 27.9% in the DEUC and PBO arms, respectively, in the overall population ( P =0.88); 15.8% and 37.0% in biologic-naïve pts; and 25.8% and 12.5% in biologic-experienced pts (Figure 2 ). Pharmacodynamic data suggest insufficient inhibition of TYK2 pathways with DEUC 6 mg BID. Incidence of adverse events (AEs) was 70.1% in the DEUC arm and 47.6% with PBO; rates of serious AEs were 9.2% (n=8) and 4.8% (n=2), respectively. Rash, acne, and worsening of UC were the most common AEs in the DEUC arm. No meaningful changes from BL in mean values of laboratory parameters were observed with DEUC treatment. Conclusion: This Phase 2 study of DEUC 6 mg BID in moderately-to-severely active UC did not meet its primary or secondary efficacy endpoints at Wk 12. In biologic-experienced pts, response rates were numerically higher with DEUC compared with PBO. The safety profile was consistent with DEUC trials in psoriasis and psoriatic arthritis.